Penafsiran QS. Al-Hujurat [49] Ayat 13 Tentang Kesetaraan Gender Dalam Al-Qur’an Menurut Quraish Shihab dan Sayyid Quthb: Studi Komparatif Atas Tafsir al-Mishbah dan Tafsir Fi Zhilalal-Qur’an - Muhammad Subki, Fitrah Sugiarto, Sumarlin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
Abstract This paper emphasizes justice and gender equality in the Qur’an. As we all know that Islam upholds the values ​​of justice and equality. Islam has arranged so beautifully. Men and women, both as servants who have the same rights, are both Caliphs on earth, have the same potential to gain achievements in various fields of science. Gender equality in the Qur’an is important to discuss because in recent years there have been many issues discussing inequality between men and women and some people consider Islam to be the culprit of the continuation of this issue. So from the authors conducted this research in order to refute the people who misinterpret Islamic teachings, especially the verse about gender equality. The research methodology used is the comparative research method, namely by comparing the opinions of Quraish Shihab and Sayyid Quthb about the interpretation of the verses of the al-Qur’an in the QS. al-Hujurat [49]: 13 relating to gender equality to get an explanation that leads to conclusions. The results of this study are that between Quraish Shihab and Sayyid Quthb, there is no difference in interpreting the verse, namely Islam greatly glorifies the position of men and women and glory in the sight of Allah swt.